Penyelesaian Utang Piutang Antara Debitur Dengan Koperasi Pegawai Republik Indonesia Guru Kecamatan Kampar (KPRI-GKK) Air Tiris - Ulfa, Aniza Nahdatul; S, Hengki Firmanda; Dasrol, Dasrol (Jurnal Ilmiah Wahana Pendidikan, 2024)
The Koperasi Pegawai Republik Indonesia Guru Kecamatan Kampar (KPRI-GKK) Air Tiris has debtors whose arrears vary from year to year. In fact, a surat pengakuan hutang or SPH which is used as a form of agreement should be able to minimize the occurrence of bad debts or failure to pay debt installments by the debtor. The purpose of this research is to determine efforts to resolve debts and Koperasi Pegawai Republik Indonesia Guru Kecamatan Kampar (KPRI-GKK) Air Tiris and to find out what factors hinder the settlement of debts and Koperasi Pegawai Republik Indonesia Guru Kecamatan Kampar (KPRI-GKK) Air Tiris. The author uses a type of sociological research, namely research on the effectiveness of current laws. This research was carried out in Air Tiris, Kampar, Riau Province. More specifically, namely at the Koperasi Pegawai Republik Indonesia Guru Kecamatan Kampar (KPRI-GKK) Air Tiris. The sample in this research was selected using a purposive technique, namely determining a number of samples that represent the existing population, namely 3 people. The data collection technique for this research is interviews, literature review. The results of this data analysis are concluded deductively, namely a way of thinking that draws a conclusion from a statement or proposition of a specific nature, from which various conclusions suggestions can be made. Based on the research results, it can be concluded that the agreement for lending and borrowing activities at KPRI-GKK Air Tiris uses a Debt Acknowledgment Letter. The management, through the treasurer, will summon debtors who do not fulfill the agreed SPH contents, then investigate what is the cause of the failure or non-payment of the debt to the cooperative. Then the cooperative will provide several alternatives, such as increasing the grace period for payment or reducing the amount paid until the SPH on the debts and receivables that have been created can be implemented and run smoothly. The way to resolve this is by resolving the dispute through non-litigation, namely a settlement outside of court. Usually called Alternatif Penyelesaian Sengketa (APS). The APS system is implemented through negotiations. The cooperative always applies the principle of kinship in every problem. Based on the research results that researchers obtained, if members do not meet their achievements, the cooperative does not terminate the agreement, does not transfer risks and does not take this matter to a judge.